Internet Memes as Stabilizers of Conspiracy Culture: A Cognitive Anthropological Analysis - Emily Godwin; Brittany I. Davidson; Tim Hill; Adam Joinson (Social Media + Society)
Internet memes have emerged as the de facto language of the internet, where standardized memetic templates and characters distill and communicate narratives in simple, shareable formats. While prior research has highlighted their broad appeal as they traverse diverse audiences, their cultural function within online communities has received less attention. To investigate this function, we draw on cognitive anthropological conceptualizations of culture and theorize internet memes as “cultural representations.” We analyze 544 memes shared across two interconnected conspiratorial subreddits about COVID-19 between 2020 and 2022, employing a combination of content and thematic analysis. In doing so, we demonstrate that community members selectively engage with standardized memetic elements that resonate with their “conspiracist worldview.” Specifically, elements conveying the enduring “cultural themes” of Deception, Delusion, and Superiority function as “cultural resources” that stabilize the community’s culture. As such, we make three contributions. First, by theorizing internet memes as cultural representations, we demonstrate their stabilizing cultural function. Second, by showing how internet memes are used in online conspiratorial communities, we highlight their role in maintaining group cohesion and alleviating contention. Finally, we advance a revised methodological approach for the study of memetic communication.